DIFFICULTY IN TRANSLATING TEXTS WITH NEOLOGISMS - Jabbarov, Ulugbek (Журнал иностранных языков и лингвистики, 2021)
As is known translation is spiritual wealth and - a kind of moral, human activity. Its origins lead us back to ancient history. It has always played a significant role in cultural history countries and world culture in general. These days, translation activities have gained an unprecedented scope thanks to increased international contacts. This fact allows some foreigners authors writing about the role of translation call our century "the century of translation." This paper purposes to explore translation theory and also some issues with translating neologisms in translation process